CSR Disclosure in Polish-Listed Companies in the Light of Directive 2014/95/EU Requirements: Empirical Evidence - Łukasz Matuszak (Sustainability, 2017)
On 15 December 2016, new non-financial reporting requirements were implemented in the Polish Accounting Act (PAA) which would be enforced from 1 January 2017. This act resulted from the transposition of Directive 2014/95/EU. New requirements oblige certain groups of entities to disclose non-financial information on environmental, social and employee-related matters, respect for human rights, anti-corruption and bribery matters. The purpose of this paper is two-fold. Firstly, this study analyses the new non-financial reporting requirements implemented in PAA, which were created from the transposition of the Directive. Secondly, this study investigates the current extent and quality of corporate social responsibility (CSR) reporting in companies listed on the Warsaw Stock Exchange (WSE) and their compliance with the new requirements. The sample comprises 150 selected listed companies on the WSE. The data were collected from annual reports, separate CSR reports, and companies’ websites. Content analysis and a rating scale were used to measure the level of CSR disclosures. The results show that companies prefer annual reports to communicate voluntary CSR disclosures. In the majority of cases, CSR disclosure of companies were not compliant with the new requirements. Companies placed little emphasis on reporting about human rights and anti-corruption. This suggests that the new reporting obligation should increase the extent and quality of non-financial disclosure among Polish listed companies.